2018
DOI: 10.1002/ccd.27894
|View full text |Cite
|
Sign up to set email alerts
|

Impact of residual coronary atherosclerosis on transfemoral transcatheter aortic valve replacement

Abstract: Objectives This study reports on the clinical effects of complete vs incompletely revascularized coronary artery disease on transcatheter aortic valve replacement (TAVR). Background There is a high prevalence of active coronary artery disease (CAD) in patients undergoing TAVR but preemptive revascularization remains controversial. Methods Patients were categorized into three cohorts: complete revascularization (CR), incomplete revascularization of a major epicardial artery (IR Major), and incomplete revascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Several studies have shown a correlation between incomplete revascularization (high residual SS) and worse clinical outcomes such as increased mortality or major adverse cardiac or cerebrovascular events (MACCE) supporting PCI in the peri-TAVI period [83][84][85][86][87][88]. However, other studies could not find an association between incomplete revascularization and clinical events [38,[89][90][91][92][93]. Recently, two important papers regarding this topic were published.…”
Section: Revascularization In Tavimentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown a correlation between incomplete revascularization (high residual SS) and worse clinical outcomes such as increased mortality or major adverse cardiac or cerebrovascular events (MACCE) supporting PCI in the peri-TAVI period [83][84][85][86][87][88]. However, other studies could not find an association between incomplete revascularization and clinical events [38,[89][90][91][92][93]. Recently, two important papers regarding this topic were published.…”
Section: Revascularization In Tavimentioning
confidence: 99%
“…Limitations in combining the results of these studies lie in differences in the definition of incomplete revascularization, follow-up times and comorbidities, and overall small patients numbers in the cohorts studied (Table 2, Ref. [16,38,[83][84][85][86][87][88][89][90][91][92][93][94]). To date, only one randomized clinical trial comparing TAVI with medical therapy vs TAVI with PCI in patients with severe AS and CAD has been performed [95].…”
Section: Revascularization In Tavimentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have quantified CAD burden with the SYNTAX score (SS) as an objective measure of CAD severity in evaluating link with TAVR outcomes [ 31 , 32 , 33 , 34 , 35 , 36 ]. In the study by Stefanini et al ., baseline and residual SS were determinants of adverse outcomes.…”
Section: Syntax Score and Outcomesmentioning
confidence: 99%
“…PCI before TAVI, on the other hand, has the potential to minimize ischemic risk during TAVI, particularly during rapid ventricular pacing, and to overcome difficulties associated with coronary access post-TAVI. Conversely, the patient remains at risk for valvular decompensation and needs to be put on dual antiplatelet therapy, which may increase the risk of bleeding during TAVI [11][12][13] . PCI after TAVI is relatively rare because prosthetic valve commissures, or stent frame, may be positioned close to coronary ostia, interfering with coronary diagnostic or guiding catheters [14] .…”
Section: Percutaneous Coronary Interventionmentioning
confidence: 99%